2015
DOI: 10.1371/journal.pone.0122010
|View full text |Cite
|
Sign up to set email alerts
|

Larval Starvation to Satiation: Influence of Nutrient Regime on the Success of Acanthaster planci

Abstract: High density populations of the crown-of-thorns seastar, Acanthaster planci, are a major contributor to the decline of coral reefs, however the causes behind periodic outbreaks of this species are not understood. The enhanced nutrients hypothesis posits that pulses of enhanced larval food in eutrophic waters facilitate metamorphic success with a flow-on effect for population growth. The larval resilience hypothesis suggests that A. planci larvae naturally thrive in tropical oligotrophic waters. Both hypotheses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
94
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(102 citation statements)
references
References 58 publications
6
94
2
Order By: Relevance
“…For example, one of the main issues facing the GBR coral reefs is the proliferation and movement of large numbers of the coral-eating Crown of Thorns starfish (COTS) [86,[108][109][110]. It has been postulated that only in periods of nutrient enrichment (river flow) are phytoplankton likely to have sufficient biomass and the correct cell type and size to support COTS larvae to a successful settlement status [66,86,110].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, one of the main issues facing the GBR coral reefs is the proliferation and movement of large numbers of the coral-eating Crown of Thorns starfish (COTS) [86,[108][109][110]. It has been postulated that only in periods of nutrient enrichment (river flow) are phytoplankton likely to have sufficient biomass and the correct cell type and size to support COTS larvae to a successful settlement status [66,86,110].…”
Section: Discussionmentioning
confidence: 99%
“…For example, one of the main issues facing the GBR coral reefs is the proliferation and movement of large numbers of the coral-eating Crown of Thorns starfish (COTS) [86,[108][109][110]. It has been postulated that only in periods of nutrient enrichment (river flow) are phytoplankton likely to have sufficient biomass and the correct cell type and size to support COTS larvae to a successful settlement status [66,86,110]. Agricultural development of the GBR catchment has increased delivery of nutrients to the GBR by several times since European settlement, and this delivery has occurred in pulses during wet season runoff events [11], resulting in large phytoplankton blooms [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite decades of research, the factors behind the boom and bust population cycles of COTS are not understood. The very high fecundity (up to 200 million eggs/female) and resilient larval stage indicate that success in the plankton is a key consideration in determining the causes of recruitment pulses [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…One of the foremost hypotheses proposed to account for outbreaks of CoTS, the larval starvation hypothesis, is predicated on a link between rates of effective larval development and availability of suitable prey (mostly unicellular phytoplankton, e.g. Lucas 1982;Okaji 1996;Uthicke et al 2015b;Wolfe et al 2015a). Early studies by Lucas (1982) suggested that rates of development and survivorship increased with increasing algal concentrations.…”
mentioning
confidence: 99%